2013
DOI: 10.1002/jmv.23653
|View full text |Cite
|
Sign up to set email alerts
|

Coinfection of hepatitis B and hepatitis delta virus in Belgium: A multicenter BASL study. Prospective epidemiology and comparison with HBV mono‐infection

Abstract: Epidemiological data on hepatitis delta virus (HDV) infection in Belgium are lacking. A multicenter questionnaire-based registry on HDV infection was collated between March 1, 2008 and February 28, 2009. It consisted of patients coinfected with hepatitis B virus (HBV) and HDV. The data samples were compared to those of a concurrent registry on HBV infection. Prospective data of patients with HBV-HDV coinfection were collected. Active HBV replication is defined as HBeAg positivity or HBV DNA > 2,000 IU/ml. Fort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…The 3.4% seropositive prevalence rate of HDVAb in HBsAg-positive U.S. veterans remains relatively low compared to rates seen in endemic regions such as the Mediterranean basis (overall 14.8% 14 , up to 45.5% in eastern Turkey 15, 16 , 44% in Tunisia 17 ), south Asia (17% in Iran 18 , 16.6% in Pakistan 19 , 8.6% in Saudi Arabia 20 ), Amazon Basin 21 and Mongolia (56–66%) 22 and is similar to rates seen in western Europe. 13, 2325 Importantly, as testing rates are quite low, it is difficult to draw conclusions about actual HDV prevalence in the US. Further studies with improved testing for high risk populations will need to be performed to characterize prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…The 3.4% seropositive prevalence rate of HDVAb in HBsAg-positive U.S. veterans remains relatively low compared to rates seen in endemic regions such as the Mediterranean basis (overall 14.8% 14 , up to 45.5% in eastern Turkey 15, 16 , 44% in Tunisia 17 ), south Asia (17% in Iran 18 , 16.6% in Pakistan 19 , 8.6% in Saudi Arabia 20 ), Amazon Basin 21 and Mongolia (56–66%) 22 and is similar to rates seen in western Europe. 13, 2325 Importantly, as testing rates are quite low, it is difficult to draw conclusions about actual HDV prevalence in the US. Further studies with improved testing for high risk populations will need to be performed to characterize prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…Even under universal HBV vaccination programs, surveillance in western Amazon should be continued to help delineate improved measures to control these infections and molecular epidemiology studies are important to define the regional pattern of endemicity. The importance of surveillance studies can be highlighted by the recent reports of high rates of HBV and HDV coinfection in developed countries mainly due to the immigration of patients from highly endemic regions and to the increased intravenous drug use [32-34]. The Amazon region attracts a significant number of migrants and tourists from all over the world and should be monitored regarding the possible introduction of different HBV and HDV genotypes that circulate in other countries, as well as their potential impact on clinical outcomes of coinfection regionally.…”
Section: Discussionmentioning
confidence: 99%
“…Compensated liver cirrhosis was present in 21% of HBV–HDV‐coinfected patients and 12% of HBV‐monoinfected cases; also, chronic active hepatitis was detected in 40·6% of patients with HBV–HDV coinfection and in 31% of HBV‐monoinfected individuals. Ho et al (), followed HBV–HDV‐coinfected and HBV‐monoinfected individuals and showed that the HBV–HDV‐coinfected cases had more advanced liver disease (Metavir score ≥ F2). In another study, 188 HBV–HDV‐coinfected patients were evaluated, 82 (43%) patients had chronic hepatitis at histology and 106 cases had a clinical/histological diagnosis of cirrhosis (Niro et al , ).…”
Section: Discussionmentioning
confidence: 99%